Associations Between the DASH Diet and Nocturnal Blood Pressure in a Sample of Chinese Elderly Subjects. (29th May 2020) - Na, Muzi; Wang, Yanxiu; Gao, Ming; Xing, Aijun; Wu, Shouling; Gao, Xiang
Abstract: Objectives: The Dietary Approaches to Stop Hypertension (DASH) diet is known to reduce daytime blood pressure (BP). This study aims to examine the relationship between DASH diet and BP monitored during sleep in a sample of Chinese old adults. Methods: A cross-sectional sample of 324 participants aged ≥ 60 years who did not take BP-lowering drugs were included (68.8% men; 70.1% with hypertension). Usual dietary intake was assessed using a validated food frequency questionnaire. The DSAH diet score was calculated based on the intake ranking of 9 dietary components. 24-hour ambulatory BP was measured and the mean and variability independent of the mean (VIM) for nocturnal systolic (SBP) and diastolic BP (DBP) were calculated. Multivariable linear regression models were constructed of each BP outcome as a function of the DASH diet score adjusting for socio-demographic characteristics (age, sex, and education), body mass index, hypertension, lifestyle factors (smoking, alcohol intake, and physical activity). The interaction between DASH diet and hypertension status was also tested in the above models. We further adjusted for three self-reported sleep parameters (duration, insomnia, snoring) to explore the potential impact of sleep on the diet-nocturnal BP relationship. Results: Mean (SD) age of subjects was 66.3 (6.0) years. There was no significant relationship between the DASH diet score and mean nocturnal SBP or DBP. However, per one unit increase of DASH diet score, nocturnal VIM-SBP and VIM-DBP were significantly reduced by −0.16 SD (95%CI: −0.30, −0.01) and −0.16 SD (95%CI: −0.28, −0.05) in the adjusted model. No significant interaction was detected between DASH diet and hypertension status. The significant associations persisted after further adjustment for the sleep parameters. Conclusions: Adherence to the DASH diet may contribute to lower nocturnal systolic and diastolic blood pressure variability in elderly people. Future studies are warrant to explore the effect of modifiable diet on blood pressure during sleep, which has significant predictive value of heart health and mortality in high-risk populations. Funding Sources: Broadhurst Career Development Professorship for the Study of Health Promotion and Disease Prevention, College of Health and Human Development, Pennsylvania State University.